Experience sampling method and the everyday experiences of adults with intellectual disability: A feasibility study. Issue 6 (31st May 2020) - Wilson, Nathan J.; Chen, Yu‐Wei; Mahoney, Natasha; Buchanan, Angus; Marks, Anne; Cordier, Reinie
Abstract: Background: Experiences of people with intellectual disability are often reported by proxy, excluding the person's own perception. To assist people with intellectual disabilities ability to communicate their own experiences, the current study explored the feasibility, reliability and validity of experience sampling methods (ESMs) for people with intellectual disability. Method: After a training session, 19 participants carried a mobile device for 7 consecutive days, answering a survey when prompted 7 times daily. Participants were interviewed at the end of data collection. Results: Excluding incomplete entries, the response rate was 33.8%, varying by living arrangement and employment. Split‐half reliability and correlations among logically linked internal experiences demonstrated strong reliability and validity. Illustration of the context of responses supported face validity. Technological and content difficulties were discussed in interviews. Conclusions: Experience sampling methods is feasible for some people with intellectual disability, providing valid and reliable information. Future research is needed to further improve feasibility.